(untitled) (Лучшие интеллектуальные исследования, 2024)
Abstract. Language transfer is one of the crucial factors in second language acquisition. Based on the language transfer theories the article analyses the language factors which affect language transfer in the process of second language acquisition from the perspective of phonetics, pragmatics and syntax in the method of comperative analyses, which can help teachers stimulate their language teaching.